Biodegradation of low-density polyethylene (LDPE) mixed with potato starch by Aspergillus niger rhizopus oryzae and their biofilms / Nurhidayah Zakaria - Zakaria, Nurhidayah (2020)
Low-density polyethylene (LDPE) is the most commonly used in plastic packaging such as for grocery bags or plastic wrap. Unfortunately, the rate of polyethylene production and consumption exceeds the rate of disposal. Several methods had been proposed to overcome this problem such as integrating this plastic material with biodegradable elements such as potato starch. However, study in degradation and decomposition of LDPE mixed with potato starch by fungi’s biofilm is limited. Thus, the aim of this study is to form biofilm of Aspergillus niger and Rhizopus oryzae for bioplastic degradation by growing in 96-well flat bottomed microtiter plate. The rate of biodegradability LDPE mixed with potato starch were analysed by using soil buried test, enzymatic activities and Fourier Transform Infrared Spectroscopy (FTIR). The rate of biodegradation of LDPE mixed with potato starch is influenced by enzymatic activities of A. niger and R. oryzae. The weight losses of LDPE mixed with potato starch during biodegradation were also determined. The percentage weight loss of LDPE mixed with potato starch in biofilm is the highest which is 0.48% compared to A. niger and R. oryzae which are 0.31% and 0.24% respectively. In short, the rate of degradation of LDPE mixed with potato starch is higher when using biofilm of A. niger and R. oryzae compared to A. niger or R. oryzae alone. Based on FTIR analysis, there are structural changes of the polymeric matrix which indicates LDPE mixed with potato starch were biodegraded by A. niger, R. oryzae and their biofilm. In conclusion, this study will give benefits to communities to solve the problems due to the abundance of plastics with a convenient, cheaper and environmentally way.